Novel FUS mutations identified through molecular screening in a large cohort of familial and sporadic amyotrophic lateral sclerosis. (15th July 2015) - Tarlarini, C.; Lunetta, C.; Mosca, L.; Avemaria, F.; Riva, N.; Mantero, V.; Maestri, E.; Quattrini, A.; Corbo, M.; Melazzini, M. G.; Penco, S.
<x xml:space="preserve">Abstract</x> Background and purpose Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease. Approximately 5%–10% of cases are familial (FALS) and the remaining are sporadic (SALS). To date FUS mutations are responsible for 4%–6% of familial cases as well as 0.7%–1.8% of sporadic cases. Methods The frequency of FUS mutations was investigated in an Italian cohort of 500 SALS and 40 FALS patients through direct sequencing of exons 5, 6, 13, 14 and 15. Results Eight FUS mutation carriers were identified in five SALS (1%) and three FALS (7.5%), five already known and three new mutations: a de novo mutation was identified in a sporadic subject as well as the co‐presence of FUS/C9ORF72 mutations in a FALS subject. The molecular and clinical details of the three patients harbouring a novel mutation (G245V, G509D and R491C) are presented here. Moreover the co‐presence of the R491C mutation and C9ORF72 pathological expansion was found according to the oligogenic disease model. Conclusions In conclusion our results revealed a higher frequency of FUS mutation carriers (7.5%) in FALS compared to literature data together with a higher presence of female gender.